2021
DOI: 10.3390/ijerph18073356
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Sources of Information on Vaccines in Spanish Nursing Students: A Cross-Sectional Study

Abstract: Health professionals are the most influential and main sources of information about vaccines for the general population, as they are regarded as role models by patients and society. The objective of the present study was to determine the knowledge and attitudes of a group of university Nursing students about vaccines, as well as their sources of information and their education needs. A cross-sectional study was performed through a questionnaire (55 items) provided to Nursing students at two Spanish universitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…The students in their final years showed a better attitude towards vaccination, a phenomenon identified in earlier studies from Spain [26,42] and other countries [11,[44][45][46]. This is probably related to the greater knowledge acquired and capacities developed by students further on in their studies.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The students in their final years showed a better attitude towards vaccination, a phenomenon identified in earlier studies from Spain [26,42] and other countries [11,[44][45][46]. This is probably related to the greater knowledge acquired and capacities developed by students further on in their studies.…”
Section: Discussionsupporting
confidence: 56%
“…The influence of being a student of nursing rather than another discipline (stronger even than the time of answering the questionnaire [Q1 or Q2]) may be explained by the fact that nurses are more involved and have greater responsibilities in vaccination programmes [29] and receive more information about, and training in, vaccination than the students of the other present degrees, and the correlation that exists between knowledge and attitude towards vaccination [11,15,42]. Other studies have reported the good disposition of students of nursing towards vaccination [26,42]. In fact, in a study performed in seven European countries, Spanish students of nursing showed the strongest disposition towards vaccination against COVID-19, followed by those studying in Italy [43].…”
Section: Discussionmentioning
confidence: 99%